Lack of seasonal variation in the incidence of eosinophilic oesophagitis in adolescent and adult non‐PPI‐responsive oesophageal eosinophilia midwestern US populations. Issue 2 (1st April 2014) - Frederickson, Nicholas W; Bayman, Levent; Valestin, Jessica; Redd, Matthew; Lee, Ye-Jin; Soubra, Mahmoud; Schey, Ron
Abstract : Background: Eosinophilic oesophagitis (EoO) has been associated with allergic disorders as well as aeroallergens. The current literature has shown a possible association between seasonal variation, mainly in the spring, and the incidence of EoO. However, this data was based on small population studies that did not exclude proton‐pump inhibitor (PPI)‐responsive oesophageal eosinophilia (PPI‐ROE) in their cohort. Aim: The aim of this study was to determine if there is a seasonal variation associated with the diagnosis of EoO in patients that had been treated with high‐dose PPI prior to diagnosis. Methods: Oesophageal biopsies were obtained from a cohort of patients who presented with symptoms of dysphagia, odynophagia, and heartburn during a 10‐year period. Symptomatic patients who had biopsies from the mid and distal oesophagus with ≥20 eosinophils per high‐power field (hpf) while on high‐dose PPI treatment for at least 5 weeks were diagnosed as having EoO. The monthly and seasonal incidences were determined (winter, January–March; spring, April–June; summer, July–September; Autumn, October–December). Results: A total of 20, 718 patients were identified and their records evaluated. From this cohort, 193 (0.93%) symptomatic patients had biopsy‐proven oesophageal eosinophilia (≥20 eosinophils/hpf) and no seasonal variation was seen in this group. However, only 57 (0.28%) had been adequately treated with PPI prior to diagnosis (i.e. non‐PPI‐ROE biopsy‐proven EoO; ≥20 eosinophils/hpf: 39 males, 18 females; age 29.5 years). The most common medical history components included asthma (12.3%) and food allergies (3.5%), and the most common presenting symptoms included dysphagia (50.9%) and heartburn (26.3%). The monthly and seasonal incidences in our cohort were with no apparent trend ( p = 0.713 and 0.703, respectively). Conclusions: The incidence of EoO was consistent across all 12 months as well as during the four seasons. Our data does not support a seasonal variation in relation to the incidence of EoO in the US midwestern non‐PPI‐ROE population.